Taiwan—A Light in the East - Pendery, David. author. aut Link
XVIII, 184 p. 31 illus.
Keywords: This book is an analytical of study of Taiwan interspersed with personal elements from the author's life there in the past 20 years. Taiwan's unique confluence of colonial histories, Chinese nationalism and democratization offers a tangible alternative to the status quo in mainland China, albeit one that is becoming increasing marginal with time. With this in mind, the author offers a concise introduction to the politics and culture of contemporary Taiwan, investigating the Taiwanese identity, aesthetic and its future. A guide to navigating the coming years for Taiwan and greater China, this book will be of interest to scholars, political scientists and historians. David Pendery is a scholar and journalist who has lived in Taiwan for over 20 years, where he teaches International Affairs, Taiwan Studies and various business and financial subjects in a Taiwanese context as an associate professor at the National Taiwan University of Business.